Parameter Estimation for Stochastic Differential Equations Driven by Mixed Fractional Brownian Motion - Na Song; Zaiming Liu (Abstract and Applied Analysis)
We study the asymptotic properties of minimum distance estimator of drift parameter for a class of nonlinear scalar stochastic differential equations driven by mixed fractional Brownian motion. The consistency and limit distribution of this estimator are established as the diffusion coefficient tends to zero under some regularity conditions.